Innovation in Energy Saving: Application for the Optimization of Consumption and the Integration of Photovoltaic Energy - Celia Tena-Pintado; Vicente A. Román-Galeano; Dorotea Dimitrova-Angelova; Diego Carmona-Fernández; Juan Félix González-González (Applied Sciences)
Nowadays, due to the considerable increase in energy demand, the reduction of CO2 emissions, the increase in energy efficiency and the lack of knowledge of the population in the current electricity system, both at residential and industrial levels, the need to implement measures that promote the common benefit of society has arisen. Photovoltaic energy has been gaining importance as a sustainable alternative to traditional energy sources, especially in Spain, where it is one of the most advantageous options thanks to its geographical location. In order to help consumers at household, SME or industrial levels to understand the complex electricity market, a new tool designed to optimize savings is presented. This application analyzes individual consumption patterns in detail and proposes savings strategies based on both tariffs and the implementation of solar photovoltaic installations. By integrating actual consumption data and PV generation estimations, the tool generates different customized scenarios, allowing the user to minimize their costs. The results of this study underline the importance of adopting renewable energy solutions, offering practical ideas for both policy makers and consumers.